DESAIN AGROFORESTRI PADA LAHAN KRITIS DI DESA KAYU LOE KECAMATAN BANTAENG KABUPATEN BANTAENG - Albasri Albasri; Samuel A. Paembonan; Syamsuddin Millang; Amar Ma'ruf (Universitas Haluoleo, 2015)
This study aims to identify the critical areas, analyze social values, assess land suitability, analyze and formulate the economic value of agroforestry design for optimal land use. The methods used in this study were the evaluation of land suitability, financial analysis, social analysis and agroforestry design on critical lands. The results showed t the land in the study site should be included in the category of critical and rather critical. The land suitability evaluation on the plant types of the agrisylviculture type for the woody plant, commodity plants is categorized in S3ehf Class (marginal suitability), one seasoned plants is categorized in S3ehfn Class. Whereas the of woody plants and commodity plants is categorized in Nrc (not suitable) and one seasoned plants are categorized in S3rcn (marginal suitability). The result of the financial analysis on the agrisyviculture type is Benefit Cost Ratio (BCR) is 2,84 and NPV Rp. 6.677.092/annual and the agrosylvopasura type is BCR of 2,48 and NPV as much as Rp. 7.885.844/annual, while maize monoculture showed a NPV of Rp. 487.247 and a BCR of 1,16. The agroforestry design based on the landscape recommended for the woody plants such as: Entrolobium cyclocarpum, Toona surenii, Gmelina arborea, planted on a ridge, the commodity plants such as: Myristica frahrans Houtt, Coffea sp, Aleurites molucana (L) Wild, Artocarpus communis Forst planted on the slopes and one seasoned plants grown on flat land. The conclusion of this research is the development of agroforestry is feasible to design agroforestry such as wood crops should be planted on ridges, MTPs crops should be planted on slopes while annual crops should be planted on flat land. Key words: agroforestry, land suitability, critical land, design